An image compression and encryption algorithm based on chaotic system and compressive sensing. (July 2019) - Gong, Lihua; Qiu, Kaide; Deng, Chengzhi; Zhou, Nanrun
Highlights: An image compression and encryption algorithm based on chaotic system and compressive sensing is presented. The bitwise XOR operation and a pixel-scrambling method controlled by chaos map are employed to change the values and the positions of the measurement results, respectively. The keys used in the chaotic systems are related to the original image and generated by the SHA-256 algorithm. Abstract: For a linear image encryption system, it is vulnerable to the chosen-plaintext attack. To overcome the weakness and reduce the correlation among pixels of the encryption image, an effective image compression and encryption algorithm based on chaotic system and compressive sensing is proposed. The original image is first permuted by the Arnold transform to reduce the block effect in the compression process, and then the resulting image is compressed and re-encrypted by compressive sensing, simultaneously. Moreover, the bitwise XOR operation based on chaotic system is performed on the measurements to change the pixel values and a pixel scrambling method is employed to disturb the positions of pixels. Besides, the keys used in chaotic systems are related to the plaintext image. Simulation results verify the effectiveness and reliability of the proposed image compression and encryption algorithm with considerable compression and security performance.